(untitled) (Journal of Fiber Bioengineering and Informatics, 2024)
This paper extracts 13 success factors based on the TOE framework in the three dimensions of Technology, Organization, and Environment (TOE). The factors are developed from investigating the challenges in the digital transformation of textile and garment enterprises and based on the literature and case studies on the success factors of digital transformation within the TOE theoretical framework. Descriptive statistics and factor analysis are performed on ample data from 201 textile and garment enterprises to verify the applicability of the TOE framework for the classification of success factors of digital transformation of textile and garment enterprises. The basic situation of the digital application of textile and garment enterprises is then summarised. The study finds that the organisational factors have the highest scores, followed by technical factors. From the observation indicators of 13 detailed success factors, the average score is greater than 4, indicating that the role of these success factors in textile and garment enterprises is generally recognised. The “digital strategic thinking” of senior managers has the highest score, followed by the “digital transformation project team.” Environmental factor scores of enterprises in the Beijing Tianjin Hebei region are the highest, followed by enterprises in the Yangtze River Delta and Pearl River Delta regions. Medium and large enterprises have higher scores for technical factors and organisational factors. Finally, the paper discusses which success factors should be addressed and improved.